2015
DOI: 10.1016/j.bpobgyn.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

What is needed for taking emergency obstetric and neonatal programmes to scale?

Abstract: Scaling up an emergency obstetric and neonatal care (EmONC) programme entails reaching a larger number of people in a potentially broader geographical area. Multiple strategies requiring simultaneous attention should be deployed. This paper provides a framework for understanding the implementation, scale up and sustainability of such programmes. We reviewed existing literature and drew on our experience in scaling up the Essential Steps in the Management of Obstetric Emergencies (ESMOE) programme in South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Specific areas that would benefit from future research include the implementation of simulation [70] and the interplay between and the role of local organisers of simulations and of simulation centres. Research would profit greatly by encouraging collaboration between practical organisers of simulations and medical education researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Specific areas that would benefit from future research include the implementation of simulation [70] and the interplay between and the role of local organisers of simulations and of simulation centres. Research would profit greatly by encouraging collaboration between practical organisers of simulations and medical education researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Supervision in the form of on-site support can improve quality of care by improving the knowledge and skills of providers (24, 25). The system of support developed in the mentoring program can inform models of national supportive supervision, which have yet to be fully developed in Laos.…”
Section: Methodsmentioning
confidence: 99%
“…In the current system, there are quarterly supervision and monitoring visits from the province to the districts, and the districts to the health centers. However, the focus tends to be observation and surveillance rather than support and capacity building, as has been noted elsewhere (25). Thus, there is an opportunity to incorporate a mentoring approach to these routine visits.…”
Section: Methodsmentioning
confidence: 99%
“…From the Kirkpatrick classification it can be concluded that sufficient evidence exists that Scaling up a training package across a health system beyond the original limited number of testing sites and maintaining the same high quality required for a scientific study remains problematic for both HICs and LMICs [82,83]. Ni Bhuinneain and McCarthy refer to a possible short-term Hawthorne effect with unsustainable outcomes on a larger scale [70].…”
Section: Future Agendamentioning
confidence: 99%
“…Policies enabling or supporting the implementation of EMONC training packages are essential [33,50,69,83], as well as supportive work environments and across-the-board participation at all levels of the health system [39]. Choosing realistic low-tech training equipment may facilitate onsite training because of a more equal distribution of available resources that can enable more appropriate training for a greater number of healthcare workers.…”
Section: Future Agendamentioning
confidence: 99%